Pharmacological investigation of Areca catechu extracts for evaluation of learning, memory and behavior in rats - Joshi, Madhusudan; Gaonkar, Kavita; Mangoankar, Sneha; Satarkar, Sneha (International Current Pharmaceutical Journal, 2012)
Areca catechu Linn is one of the stimulant masticatory crude materials of Indian system of medicine. The present study was done to evaluate the effect of Areca catechu Linn extract on learning and memory in rats using radial arm maze. The extract used for study was of two different types of Areca catechu namely, wet and dried Areca catechu. Three groups of rats each consisting of seven animals were used for the purpose. Test groups were given 500mg/kg p.o of wet Areca catechu extract and dried Areca catechu extract respectively. It was observed that wet Areca catechu extract showed greater increase in spatial memory and learning in comparison to the control group of rats. Hence increase in spatial memory could be because of higher amount of arecoline present in wet Areca catechu extract. DOI: http://dx.doi.org/10.3329/icpj.v1i6.10533 International Current Pharmaceutical Journal 2012, 1(6): 128-132